Laparoscopic Splenectomy to Salvage Renal Transplants from Severe Acute Antibody-Mediated Rejection - Michael Latzko; Sakshi Jasra; Sana Akbar; Harry Sun; Sadanand Palekar (Case Reports in Transplantation)
Purpose. Acute antibody-mediated rejection, a complication of cross match positive and sensitized renal transplants, occurs despite the use of standard desensitization protocols. Rescue therapy consists of plasmapheresis and intravenous immunoglobulin (IVIg). In patients with preformed donor specific antibodies, rejection can be aggressive. We report here a case in which laparoscopic splenectomy was added to the standard rescue regimen. Case Report and Results. A 40-year-old Hispanic female with end stage renal disease had been receiving hemodialysis. The patient had numerous class 1 unacceptable antigens. She was scheduled to undergo an incompatible 1-1-1 mismatch living related donor kidney transplant. Preoperatively, the patient received plasmapheresis, IVIG, and thymoglobulin. There was good graft function until postoperative day 5. At that point, worsening renal function was noted. Renal biopsy was consistent with AMR. The patient became anuric and dialysis was initiated. To salvage the transplant, the patient underwent laparoscopic splenectomy. Postoperatively, renal function improved. Two years after transplant, the patient continues to have excellent graft function. Conclusion. In a small but significant number of renal transplants, antibody production occurs at a rate that traditional treatments are unable to reduce effectively. Based on our experience, the addition of splenectomy to standard rescue therapy can salvage renal transplants.